Dynamic analysis of functionally graded viscoelastic beams on the elastic foundation under multiple moving loads - Lien, Tran Van; Ha, Le Thi (Vietnam Journal of Mechanics, 2025)
In this paper, the dynamic analysis of the Functionally Graded (FG) simply supported beam resting on the Winkler–Pasternak elastic foundation under multiple moving loads is investigated by using Timoshenko beam theory and the Kelvin–Voigt damping model. The material properties of the FG beam vary continuously in the thickness direction. The Mori–Tanaka homogenization model is used to determine the effective material properties of the FG beam. Equations of motion for the beams are established based on the Finite Element Method (FEM). The effects of different material distributions, velocities of multiple moving loads, distances between loads, and damping on the dynamic responses of the beam are discussed.